Promoting institutional collaboration through a joint project-based learning course: a case study of upper secondary school and university students’ experienced relevance - Ikävalko, Topias; Pernaa, Johannes; Haatainen, Outi; Aksela, Maija (Frontiers in Education, 2024)
There is a great need to develop research-based models for supporting collaboration between educational institutions. Collaboration models are needed, for example, to assist the transition from lower educational level to higher education or from higher education to working life. In this research, collaboration was conducted through a joint upper-secondary school and university course that addressed global challenges by using a project-based learning approach. There is a shortage of research exploring students' perceptions of collaboration. Therefore, the main purpose of this qualitative case study is to explore the relevance of the joint course for upper secondary school students and university students. The research was guided by the following research question: What kind of relevance did the students experience in the joint project-based learning course? The data was gathered using questionnaires, interviews, and reflective study reports. The data was analyzed via theory-based content analysis where research-oriented relevance model was used as the analysis framework. The analysis framework enabled categorizing experienced relevance on individual, vocational and societal dimensions. Altogether, the analysis produced 7 relevance categories for upper-secondary students and 9 for university students. According to the analysis, upper-secondary school students felt that the course offered the most on an individual relevance dimension whereas university students experienced the vocational relevance dimension most diverse. As the main conclusion, this research produced new insights on the experienced relevance of upper-secondary level and higher education cooperation from the students' point of view. The acquired knowledge can be useful for everyone developing new cross-institutional cooperation models.